Right-sided diverticulosis is an independent risk factor for bleeding in patients admitted for diverticular disease. Issue 7 (July 2021) - Arena, Rosario; Lisotti, Andrea; Mussetto, Alessandro; Merighi, Alberto; Pezzoli, Alessandro; Triossi, Omero
Abstract: Background: Diverticular bleeding is the main cause of lower gastrointestinal bleeding in both Eastern and Western countries. Several risk factors have been identified, such as comorbidities and concomitant medications. In Eastern population, the prevalence of right-side diverticulosis is higher than in Western one, and some Authors identified bilateral diverticulosis as a risk factor for bleeding. Aims: To identify risk factors for diverticular bleeding in patients admitted for diverticular disease (DD). Methods: All patients admitted for DD from January 2017 to December 2018 were retrieved from the hospital Information System. For each patient, age, gender, clinical presentation and concomitant medication were recorded. All patient underwent imaging assessment (computed tomography, ultrasound or MRI) and colonoscopy during hospitalization or within one month. Results: Among 1248 patients discharged with a diagnosis of DD during the study period, 293 (52.2% male, median age 75 years) were finally analyzed; of them, 105 (35.8%) for diverticular bleeding. On multivariate analysis, male gender (OR 4.27), age (OR 1.12), anti-thrombotic medications (OR 2.60) and right-sided DD (OR 5.70) were independently correlated to diverticular bleeding. Conclusion: Our study provides evidence that, together with age, male gender and concomitant anti-thrombotic treatment, right-sided DD represents an independent risk factor for bleeding.